The Implementation of Audio Visual as Media to Increase Speaking Skill: The implementation of audio-visual media in the classroom - Mislawi Yadi (JOEY: Journal of English Ibrahimy, 2022)
This research was classroom action research (CAR) which focuses on the implementation of audio-visual media in the classroom. The method in this study was qualitative descriptive that used by the Kemmis and Mc Taggart method which involves four components, such as: (1) Planning (2) Action (3) Observation and (4) Reflection. The object of this research were students collage at the second semester. Total participants in this study were 11 students. The researcher was a subject (researcher and actor in the study). The implementation of Audio-visual media were carrying out for 3 cycles. The result of this application were increasing English language skill with the right language rule. By using Audio Visual, the students directly imitated the speaker's language style, such as; conversation, pronunciation, accent, mimicking, gestures, intonation, the use of words and sentences that used on communication. This result support with previous research that reading, listening, seeing and practicing will be easier to remember and learn. By using audio-visual media, it can mediate learning to master the four components in scientific understanding in learning English language.